Effect of ketogenic diet and other dietary therapies on anti‐epileptic drug concentrations in patients with epilepsy. (18th June 2017) - Heo, G.; Kim, S. H.; Chang, M. J.
Summary: What is known and objective: The ketogenic diet (KD) is an effective high‐fat, adequate‐protein, low‐carbohydrate diet for patients with refractory epilepsy. The aim of this study was to investigate the potential effects of the KD and other dietary therapies on the concentrations of anticonvulsants in patients with epilepsy. Methods: Patients with epilepsy who were treated with the KD and other dietary therapies for more than 30 days with at least one measurement performed both before and during the diet were evaluated. The mean serum concentrations and the mean serum concentrations per weight per daily dose per bioavailability (F) of anti‐epileptic drugs (AEDs) before and during the treatment were assessed. We also compared the rates of events out of reference ranges of the AEDs between before and during the KD and other dietary therapies. We compared the serum albumin, alanine transaminase and aspartate transaminase data of patients with valproic acid before and during the KD. Results and discussion: One‐hundred thirty‐nine patients including 81 male patients were enrolled. The median age of the patients was 2.91 (0.15‐15.46) years. The median duration of the dietary therapies was 153 (35‐2307) days. After the dietary therapies, the serum concentrations of carbamazepine, lamotrigine, levetiracetam, topiramate and valproic acid decreased, whereas that of phenobarbital slightly increased. However, statistical significance was found only with valproic acid (67.07±25.89 μg/mL vs 51.00±20.19 μg/mL, P <.05). The serum concentrations per weight per daily dose per drug F significantly decreased for valproic acid (1.38±1.39×10 −2 vs 0.82±0.82×10 −2 μg d mL −1 F −1 ) and phenobarbital (6.66±7.20×10 −2 vs 4.75±4.07×10 −2 μg d mL −1 F −1, P <.05). The rate of occurrence of events out of reference ranges significantly increased with valproic acid (36.08% vs 57.23%, P <.05). What is new and conclusions: Most anti‐epileptic drug serum concentrations remained stable during the KD and other related dietary therapies except those of valproic acid. Therefore, serum concentrations of valproic acid should be monitored when the KD and other dietary therapies are concomitantly administered. Abstract : Only serum concentrations of valproic acid were significantly decreased during the ketogenic diet. The rate of occurrence of events out of reference ranges significantly increased with valproic acid during the ketogenic diet. B, before the ketogenic diet; D, during the ketogenic diet.